Standing tall : the stories of ten Hispanic Americans - Palacios, Argentina (New York : Scholastic, 1994)
Presents photographs and stories of ten American heroes, influential and important Hispanis-American women and men from very different backgrounds and times who made history and are still making it.
Z
1060
Z
Keywords: Hispanic Americans -- Biography -- Juvenile literature; Hispanic Americans